PERTIMBANGAN HAKIM DALAM MENJATUHKAN PUTUSANTERHADAP TERDAKWA PELAKU PENCABULAN YANG DILAKUKAN OLEH ANAK (Putusan Nomor 38/Pid.Sus-Anak/2021/PN.Pdg) - Ifing, Baso; Anshar, Sayid (Ensiklopedia Education Review, 2023)
The crime of sexual abuse committed by children is regulated in Law Number 35 of 2014 concerning Child Protection and Law Number 11 of 2012 concerning the juvenile criminal justice system (SPPA). The recent rise in cases of criminal acts of sexual abuse committed by children has become very worrying. In accordance with applicable laws and regulations. Law enforcers are obliged to seek diversion for children involved in criminal acts, but in the case of children who commit criminal acts of sexual immorality, diversion cannot be attempted. In the case of children as perpetrators of sexual abuse, it is certainly not easy to decide on sanctions against them, considering that they still have the rights to grow and develop. The judge's considerations in handing down a decision against the perpetrator of sexual abuse committed by a child based on Number 38/Pid.Sus-Anak/2021/PN.Pdg consist of: Juridical considerations, namely the indictment which is the legal basis in criminal proceedings, witness testimony is the main consideration taken into consideration by the judge in the decision, the defendant's statement is what the defendant stated at trial was valid evidence, as well as the evidence that the defendant used in the theft. Non-juridical considerations are the background of the defendant who did it due to economic factors, lack of understanding about religion and belief, the application of crimes against perpetrators committed by children based on Number 38/Pid.Sus-Anak/2021/PN.Pdg has been regulated in article 81 paragraph ( 2) in conjunction with article 76E of Law Number 17 of 2016 concerning the stipulation of government regulations in lieu of Law of the Republic of Indonesia Number 1 of 2016 concerning the second amendment to Law Number 23 of 2002 concerning child protection and Law Number 8 of 1981 concerning Law criminal procedures and other relevant laws and regulations”, Sentencing Adrian Rahma Doni's child Rian for 1 (one) year and 3 (three) months.Keywords: Judge's Consideration, Crime of Obscenity, Juvenile Justice System